An evolutionary condensation sequence revealed by mineralogically-distinct nodules in fine-grained, spinel-rich inclusions from CV3 chondrites: Implications for the genetic links between different types of non-igneous refractory inclusions. (1st September 2021) - Che, Shaofan; Brearley, Adrian J.
Abstract: Fine-grained, spinel-rich inclusions (FGIs) are abundant in CV3 chondrites and exhibit textures and compositions that are consistent with a condensation origin. We have conducted a systematic investigation of FGIs from two reduced CV3 chondrites, Leoville and Efremovka, which has revealed a number of microscale variations in the primary mineralogies and textures of nodules, and provided further insights into the origins of FGIs. Nodules in individual FGIs vary in size and exhibit variations in their mineralogical zonation, resulting in significant heterogeneity within each FGI. In individual FGIs, nodules with a small size (typically < 10 μm) commonly form clusters, whereas larger nodules (often > 20 μm) are either embedded in the mass of small nodules or occur as shells surrounding clusters of small nodules. The size difference is associated with a difference in mineralogy: small nodules typically contain single or a few spinel/melilite grains as cores, while the spinel/melilite cores of large nodules are polycrystalline and more compact. Transmission Electron Microscope observations show that the nodules have complex microstructures, including the presence of fine-grained spinel, the close association of fine-grained Al-Ti-diopside with spinel, and a crystallographic orientation relationship between adjacent clinoenstatite and diopside grains. Our microstructural observations indicate that disequilibrium condensation played an important role in the formation of FGIs, consistent with some previous studies. Specifically, the presence of spinel-cored and melilite-dominant nodules, as well as the different occurrences of spinel (in the cores and on the periphery), suggest that formation of these nodules occurred under disequilibrium conditions, which may be caused by physical isolation of condensates. Nodules in FGIs show textural and compositional similarities with other types of non-igneous CAIs: hibonite-spinel inclusions and fluffy Type A CAIs. We suggest that mineralogically-distinct nodules are micrometer-sized counterparts of different types of non-igneous CAIs and record an evolutionary condensation sequence in the solar nebula. It is likely that different nodules in individual FGIs formed in the same gaseous reservoir, but at different times. The mechanism of physical isolation of condensates probably controlled the accretion behavior of nodules with different mineralogies and sizes, resulting in the observed distribution patterns of nodules. On the other hand, some mineralogically-zoned FGIs, with a Mg-rich core and a Ca-rich mantle, can be better explained by condensation, followed by transport of the inclusions to a different region of the protoplanetary disk.